PC.72 Neonatal Outcomes Following Rotational Instrumental Delivery. (9th June 2014) - Redwood, E; Alomar, O; Stephen, G; Conroy, R; Vause, S; Tower, C
Abstract : Introduction: Rotational instrumental delivery has previously been associated with adverse neonatal outcomes. Since a 1979 study demonstrated 3.49% neonatal mortality associated with Kielland's forceps there has been a gradual decline in its use, which also coincided with a rise in Caesarean section rate. The objective of this study was to report neonatal outcomes following rotational instrumental delivery. Methods: Data was collected retrospectively from 1110 rotational instrumental deliveries conducted at St Mary's Hospital, Manchester between April 2009 and February 2012 for neonatal intensive care (NICU) admission, jaundice, cooling, sepsis, injuries, ventilation and mortality. Results: Data was available for 1023/1110 (92%) deliveries. Numbers of babies with jaundice, cooling, sepsis, injuries, ventilation or mortality were low and not different between rotational methods. More babies delivered by ventouse needed NICU admission; 30/283, 10.6% compared to 48/692, 6.9% babies delivered using either method of forceps (p = 0.030 chi squared). 3/53 failed instrumental deliveries resulted in neonatal injury (5.6%), compared to 14/637 (1.4%) for successful instrumental delivery (p = 0.056). There was no significant difference between any of the neonatal outcomes in babies delivered by consultants compared to more junior training grades. Conclusion: For prolonged second stage of labour secondary to malposition, rotational instrumental delivery is a safe option in terms of neonatal outcomes. Differences in method of delivery were marginal, with ventouse being more likely to result in second instrument use and NICU admission.